Efficient biodegradation of phenanthrene using Pseudomonas stutzeri LSH-PAH1 with the addition of sophorolipids: Alleviation of biotoxicity and cometabolism studies. (15th May 2022) - Luo, Chengyi; Hu, Xin; Bao, Mutai; Sun, Xiaojun; Li, Fengshu; Li, Yiming; Liu, Wenxiu; Yang, Yan
Abstract: Phenanthrene (PHE) is widely distributed, and it can cause genotoxicity in humans by interacting with enzymes in the body. A current challenge for PHE bioremediation is the inhibitory effect of biotoxic intermediates on bacterial growth. Notably, the aerobic biotransformation processes for PHE in the presence of sophorolipids have been poorly studied. Here, a PHE-degrading strain was isolated from sediments and identified as Pseudomonas stutzeri and named LSH-PAH1. It was observed that 1-naphthol (a biotoxic substance that can inhibit strain growth) was produced during the PHE metabolism process of LSH-PAH1. The biodegradation ratio increased from 21.4% to 91.7% within 48 h after the addition of sophorolipids. Unexpectedly, this addition accelerated the metabolic process for 1-naphthol rather than causing its accumulation. The cometabolism of 1-naphthol and sophorolipids alleviated the biotoxic effects for the strain, which was verified by gene expression analysis. We identified a new PHE-degrading strain and provided a mechanism for PHE biodegradation using LSH-PAH1 with the addition of sophorolipids, which provides a reference for practical applications of the bioremediation of PHE and study of the cometabolism of biotoxic intermediates. Graphical abstract: Image 1 Highlights: Biotoxic substances during biodegradation can be co-metabolized with sophorolipids. The biodegradation ratio of PHE reached 91.7% with sophorolipids-assisted in 48 h. Sophorolipids can be used as both biosurfactants and carbon sources. The addition of sophorolipids stimulates the expression of related genes.